Emerging role of the RNA-editing enzyme ADAR1 in stem cell fate and function - Di Lu; Jianxi Lu; Qiuli Liu; Qi Zhang (BMC, 2023)
Abstract Stem cells are critical for organism development and the maintenance of tissue homeostasis. Recent studies focusing on RNA editing have indicated how this mark controls stem cell fate and function in both normal and malignant states. RNA editing is mainly mediated by adenosine deaminase acting on RNA 1 (ADAR1). The RNA editing enzyme ADAR1 converts adenosine in a double-stranded RNA (dsRNA) substrate into inosine. ADAR1 is a multifunctional protein that regulate physiological processes including embryonic development, cell differentiation, and immune regulation, and even apply to the development of gene editing technologies. In this review, we summarize the structure and function of ADAR1 with a focus on how it can mediate distinct functions in stem cell self-renewal and differentiation. Targeting ADAR1 has emerged as a potential novel therapeutic strategy in both normal and dysregulated stem cell contexts.